Application of AI in Cloud Computing - Kumar Kishan Chandra; Dr. Manisha Kumari Deep (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
AI in cloud computing is a growing field that focuses on creating intelligent solutions for many industries. AI cloud computing enables companies to create dynamic applications by providing machine learning and analytics tools to perform advanced tasks. AI cloud computing focuses on creating these intelligent applications to help businesses use big data, provide systems for advanced operations, and predict and forecast future growth. Do it. This leads to good profitability and long-term operation of the business. This white paper examines the evolution of cloud computing, its benefits for small and large businesses, the latest business trends, use cases, and future predictions.